Influence of microwave pre-treated Palm Kernel Shell and Mukah Balingian coal on co-gasification - R. Ahmad; M. A. M. Ishak; K. Ismail; N. N. Kassim (Journal of Mechanical Engineering and Sciences, 2019)
In this study, microwave irradiation pretreatment of palm kernel shell (PKS) and Mukah Balingian (MB) coal was carried out in a fixed bed reactor. The effect of microwave power and processing time was investigated on pretreated PKS and MB coal characteristic. Then, the co-gasification of microwave pretreated PKS and MB coal was conducted to examine the effect of product yield and gases composition. The results showed that, the characteristics of pretreated sample was improved with increasing microwave power and processing time. The volatile matter, oxygen content and O/C ratio of pretreated sample decreased, while the calorific value, fixed carbon and carbon content of pretreated sample increased with increasing microwave power. The carbon content of pretreated PKS was closed to the untreated MB coal with comparable calorific value was obtained. The microwave power level of 450 W and processing time of 8 min were appropriate to upgrade the PKS and MB coal for co-gasification. The pretreated sample produced higher gas yield and lower tar and char yield than the untreated sample during co-gasification. This result was due to low moisture and oxygenated compound of pretreated feedstock made it appropriate to be converted in co-gasification. Moreover, co-gasification of pretreated sample produced the higher H2+CO and CH4 and lower CO2 composition than untreated sample. Thus, it can be concluded that the microwave irradiation pretreatment on PKS and MB coal performed the significant impact on the product distribution and composition during the co-gasification.